Kontestasi Persaingan Program Acara Berita dalam Bisnis Media Televisi - Rahayu Rahmadini (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2019)
This paper aims to explain the contestation among news programs in deal with a television media business. This research appropriated the Media Economic Theory derived from Vincent Moscow and the Theory of Media. The research uses a postpositivism paradigm. This paper follows a descriptive-qualitative approach. Findings: the contestation among news programs has a good and quality competition of television media business. And also, this research explains how broadcastiong station strategy can produce a program to reach an success and beyond a rivality in similar program that propose by the other broadcasting station.